2016
DOI: 10.5455/aim.2016.24.267-270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Relationship Between Thyroid Nodule Size with Malignancy and Accuracy of Fine Needle Aspiration Biopsy (FNAB)

Abstract: Introduction: Some studies have shown largest thyroid nodule size, especially ≥4cm that can predict malignancy and reduce fine needle aspiration biopsy (FNAB) accuracy. Therefore, this study is designed to evaluate relationship between thyroid nodule sizes with malignancy and its effect on FNBA accuracy. Materials and Methods: a retrospective analytical study design aims to investigate all patients Positive and negative results of FNAB in all nodules were 3.5% and 6.3%, in <4cm nodules were 5.8% and 6.2% and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
1
12
1
Order By: Relevance
“… 9 , 13 Conversely, Godazandeh et al . reported that in younger patients the prevalence of thyroid carcinoma is higher 16 , and in another study surgery without rFNA is recommended for younger patients. 14 Latter findings are in concordance with our results that younger age is a significant independent factor for malignancy in this Bethesda diagnostic category.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 9 , 13 Conversely, Godazandeh et al . reported that in younger patients the prevalence of thyroid carcinoma is higher 16 , and in another study surgery without rFNA is recommended for younger patients. 14 Latter findings are in concordance with our results that younger age is a significant independent factor for malignancy in this Bethesda diagnostic category.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, this could be because of a selection bias based on younger patients being referred to surgery more often in our study, though this finding was not statistically significant. Nodule size is reported to have no predictive value of malignancy and it should not be used as a reliable factor for clinical decision making 16 , 17 , although Kamran et al . suggest a threshold of approximately 2 cm in nodule diameter with strong evidence that size > 2 cm is associated with an increased risk of well-differentiated thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other study concludes that male gender, age ≥60 years old, microcalcification, cervical lymphadenopathy was risk factor of malignancy. [4,[8][9][10] Based on benign cytology features and low false negative rate of the FNAC patient required regular follow up with annual clinical examination and repeat ultrasound. Repeat cytology was recommend for patient with abnormal feature in ultrasound and changes in the size of the nodule.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid nodules are very common in the general population and can be found clinically in 4-7% of the general population. However, it seems that the true prevalence of thyroid nodules is higher (the prevalence is from 8 to 65% in autopsy and from 19 to 35% in ultrasound survey) [1,2]. Although most thyroid nodules are benign hyperplastic lesions, past research has determined that thyroid cancer occurs in 5 to 15% of thyroid nodules [3][4][5].…”
Section: Introductionmentioning
confidence: 99%